Occupational-related Stress among University Faculty Staff in Kwara State, Nigeria: Outcomes on Goal Achievement (Quest Journal of Management and Social Sciences, 2020)
Background: Incidents of occupational stress among academicians globally is on the rise, despite its impending effects and prospects of coping strategies suggested in literature.Objective: This study examines occupational stress among university faculty staff and its outcomes on university goal achievements in Kwara State, Nigeria. Methods: The study was a cross-sectional survey. A multi-stage sampling technique was used for the selection of 458 faculty staff. Data were collected with the use of a 57-item questionnaire.Results: Results reveal that the level of stress among faculty staff was high (3.25), while stress level differs based on gender (p